EXTENSION OF RIGHTS FOR BUILDING BY THE LIMITED LIABILITY REVIEWED FROM LEGAL CERTAINTY, JUSTICE AND TOWARDS SUSTAINABLE INVESTMENTS AND PEOPLE’S WELFARE - I Nyoman Alit Puspadma (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2013)
ABSTRACTUUPA HGB regulates the extension of Article 35 paragraph (2), which containsfuzziness norm. The word "may" in norms in the article lead to different interpretations, so contrary to the provisions of Article 5 of Law No. f letters. 12 in 2011, which ordered that in every formation a good rule, one of the requirements that must be met is "clear statement". Regarding the subject of HGB stipulated in Article 36 paragraph (1) UUPA, which is a. Citizens, and b. legal entities established under Indonesian law and domiciled in Indonesia. Legal entity used in this study is a limited liability company (PT). In that regard there are three problems examined, namely: How does extension HGB werearranged? How to interpret the provisions of Article 35 paragraph (2) if it is associated with UUPA kepastia principles of law, keadian, and continued investment towards social welfare, as well as the legal consequences for HGB PT when the extension is rejected? Theory is used to analyze the hierarchy theory Norma (stuffen theory), the theory of legal certainty, justice theory, and the theory of the Welfare State, while the research method used in accordance with the normative legal research is a method of approach to legislation (statute approach), approaches the concept (conceptual approach), and analytical approaches (analytic approach), with the source material in the form of the lawof primary legal materials, secondary and tertiary. Once analyzed, the conclusion is as follows: extension HGB above TN stipulated in Article 35 paragraph (2) UUPA conjunction with Article 26 paragraph (1) 1996 PP 40 in conjunction with Article 40 PMNA / KBPN 9, 1999, while the extension of HGB over HPL occurred after the approval of the shareholders of HPL stipulated in Article 35 paragraph (2) UUPA Article 26 paragraph (2) 1996 PP 40 in conjunction with Article 45 PMNA / KBPN 9, 1999. HGB on land ownership is set to be extended, but in accordance with Article 29 paragraph (2) PP 40 epidemic in 1996 may be updated. Interpret the provisions of Article 35 paragraph (2) UUPA should always be associated with Article 2 (3) and Article 3 of the Capital Market Law UUPA. In terms of HGB expires, the land is returned to the States when coming from TN or holder if 2 the land comes from HPL HPL, and PT was no longer able to use the land as a place of business (investing). If PT does not get land to run his business (investment), then there will be other legal consequences, namely: PT dissolution, and laid off employees, which will lead to other consequences, such as economic and social consequence.Key Words : Extension Of Rights For Building, Company Limited Liability, Legal Certainty, Sustainable Investments, People's Welfare